Synthesis of Enaminones by a Palladium-Catalyzed Four-Component Carbonylative Addition Reaction - Wang, Liangguang; Ma, Juan; Chen, Xia; Zhou, Xiaoyu (Synlett, 2017)
A palladium-catalyzed carbonylative addition reaction of aryl bromides, amines, and alkynes has been developed. The reaction occurs readily in N,N-dimethylformamide with PdCl2(PPh3)2 as a catalyst to give the corresponding enaminones in medium to excellent yields. Furthermore, a mechanism for the palladium-catalyzed four-component carbonylative addition reaction is proposed.
Keywords: palladium catalysis; multicomponent reaction; carbonylative addition; enaminones; aryl bromides; amines